PENGARUH GROWTH OPPORTUNITY, NET WORKING CAPITAL, CASH CONVERSION CYCLE TERHADAP CASH HOLDING - Marisa Kesia Isabella; Susanto Salim (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This study aims to determine the factors that influence cash holding, which consists of growth opportunity, net working capital, and cash conversion cycle. This study uses 89 samples of manufacturing companies listed on the Indonesia Stock Exchange during 2017-2019. This research was selected by purposive sampling method and data processing technique used the EViews version 10.0 software. The results of this study indicate thatgrowth opportunity has no significant positive effect on cash holding, net working capital has a significant negative effect on cash holding, and the cash conversion cycle has no significant negative effect on cash holding. The implication of this research is that the existence of a relationship between growth opportunity, net working capital, and cash conversion cycle on cash holding, can help companies avoid financial difficulties or conditions that cause company losses.